Effect of Socratic Questioning Technique in tackling the Cognitive Distortions of Senior Secondary Students in Abuja, FCT. - FAGBOHUN, Raphael Seun (dialektika kontemporer, 2025)
This study examined the effect of Socratic Questioning Technique (SQT) on the Cognitive distortions of senior secondary students (SSS) in Abuja, Federal Capital Territory (FCT), Nigeria. SQT is one of the Cognitive Behavioral Therapy (CBT)’s techniques. An experimental design using purposive and random sampling methods was used to conduct the study. The sample population consists of one hundred and twenty (120) SSS of OCAC College, Abuja, FCT, Nigeria. The research instrument, the In-School Adolescents’ Cognitive Distortion Questionnaire (ISACDQ), was administered and students’ scores determined their assigned group before and after the therapy. The data for the study were analyzed using t-test and one way Analysis of Variance (ANOVA) with the acceptance level of probability value for each test fixed at 0.05. The result of the data analysis revealed that SQT was effective in tackling the cognitive distortions of SSS without the interference of gender, religion and class/year of study. Based on findings from this study, it is evident that psychotherapeutic interventions in schools are relevant and beneficial to the academic achievements of students.